An Attribution Theory Lens on Plagiarism: Examining the Beliefs of Preservice Teachers (Canadian Perspectives on Academic Integrity, 2023)
Academic misconduct is a prominent issue at postsecondary institutions. This issue includes the act of plagiarism, which has received considerable attention on campuses. There is a growing body of research examining why students engage in plagiarism, and what they know about plagiarism, but little of this research is guided by a theoretical framework. Although all students may be tempted to plagiarize, students in teacher education programs represent a unique population because they are concerned with developing their own academic performance alongside the skills necessary to manage situations of academic misconduct as future teachers. Therefore, our first aim was to examine preservice teachers’ beliefs about plagiarism. Then, following the principles of Attribution Theory, our second aim was to investigate how beliefs of controllability related to acts of plagiarism impacted participants views on responsibility, emotions, help giving, and reporting. We used a within-person repeated measures design with three levels of controllability manipulated through hypothetical scenarios of plagiarism to collect data from 201 preservice teachers. Overall, preservice teachers had strong beliefs about plagiarism. Moreover, when scenarios included students who engaged in plagiarism that was controllable, participants were more likely to view the student as responsible, feel anger towards them, support punishment, and recommend reporting the student, than when the act of plagiarism was not seen as controllable. We provide recommendations for instructors and administrators for supporting students and highlight limitations and directions for future research.